Li-Fraumeni syndrom - návrh komplexní preventivní péče o nosiče TP53 mutace s použitím celotělové magnetické rezonance - Foretová, L; Stěrba, J; Opletal, P; Mach, V; Lisý, J; Petráková, K; Palácová, M; Navrátilová, M; Gaillyová, R; Puchmajerová, A; Křepelová, A; Macháčková, E (Klinicka onkologie, 2012)
Li-Fraumeni syndrome (LFS) is one of the most serious hereditary cancer syndromes with high risk of malignancy already in childhood. Adrenocortical carcinoma, brain tumor, leukemia, sarcoma are the most frequent malignancies in children. Early breast cancer, brain tumor, sarcoma, skin cancer, gastrointestinal, lung, gynecological, hematological and other malignancies can be seen in adults. Predictive testing in families with detected LFS and TP53 mutation is offered from the age of 18 for various reasons. One of the most important reasons is a very limited effectivity of prevention especially in children, also the possible risk of psychological harm to the child and his family caused by the diagnosis of this syndrome. Progress in diagnostic methods, especially total body MRI, enables to propose preventive care for early cancer diagnoses for children and adults. Biochemical tests, ultrasound, MRI may improve survival of these high risk individuals and support the possibility of predictive testing in children.
Keywords: Heterozygote; Magnetic Resonance Imaging; Liův-Fraumeniho syndrom; geny p53; mutace; magnetická rezonanční tomografie; heterozygot; Humans; Mutation; Whole Body Imaging; celotělové zobrazování; lidé; Genes, p53; Li-Fraumeni Syndrome